Лексико-семантичне поле «патріот» у листах Б.Грінченка з України Наддніпрянської - Антіпов, Олег; Antipov, Oleg (Східноєвропейський національний університет імені Лесі Українки, 2013)
Предметом аналізу в статті є публіцистична спадщина, а саме листи, Б. Грінченка, на матеріалі яких здійснено дослідження лексико-семантичного поля «патріот», що складається з трьох мікрополів, виокремлено лексеми, семеми та семи, якими письменник збагатив досліджуване поле.Art publicistic, which is created by writers, whose thoughts are depicted on paper, is characterized by direct interference in life of the society. By means of letters as a publicistic genre is formed public mind, there is an influence on national orientated personality, and the questions of vital importance are solved, which the writer is worried and interested about. The subject of analyzes of article are publicistic letters of great Ukrainian writer and publicist of the end XIX and the beginning XX centuries B. Hrinchenko which reveal his views on problems of the national and cultural Renaissance that time. Specific of letters from Ukraina Naddniprianska is characterized in the article, raised in them problems; on their material is researched lexical and semantic field «patriot», which consists of three micro-fields («patriot as he is», «pseudo patriot» and «anti patriot»). Also were marked lexemes which are represented it, sememes and semes, by means of them writer enriched it.
Lexical and Semantic Field «Patriot» in Boris Hrinchenko’s Letters from Ukraina Naddniprianska
Keywords: лексико-семантичне поле; мікрополе; лист; патріот; лексема; сема; lexical and semantic field; micro field; letter; patriot; lexeme; seme